Nursing work during the COVID-19 pandemic: (dis)satisfaction and (de)motivation - Letícia de Assis Santos; Allana de Lacerda Uzeda; Luana Ramos Garcia; Maithê de Carvalho e Lemos Goulart; Fernanda Garcia Bezerra Góes; Janaina Luiza dos Santos (Universidade Federal do Ceará, 2023)
Objective: to show the factors that lead to (dis)satisfaction and (de)motivation in the work of nursing professionals in the COVID-19 pandemic. Methods: qualitative study, developed virtually, with professionals from nursing teams. Data was processed using the software Interface de R pour Analyses Multidimensionnelles de Textes et de Questionnaires and analyzed according to Thematic Analysis. Results: 72 workers participated. 45 (62.5%) stated to be satisfied and 46 (63.9%) to be motivated for work. The text segments were separated into four classes, each showing a factor that interfered in work (dis)satisfaction and (de)motivation. Conclusion: factors that intervene in satisfaction and motivation were mostly associated with patient recovery and helping one another. Among the factors that impacted on dissatisfaction and demotivation, the lack of needed supplies and work overload stood out. Contributions to practice: we identified needs and strategies relevant to improve the work environment.